Hepatic lipidosis in nine African white-bellied pangolins (Phataginus tricuspis) from a North American zoologic institution - Horgan, Molly; Landolfi, Jennifer; Stacy, Nicole I.; Watts, Jennifer; Aitken-Palmer, Copper (Frontiers in Veterinary Science, 2025)
IntroductionThe African white-bellied pangolin (Phataginus tricuspis) is an endangered species with a small population under managed care in the United States. Over the course of 4 years, nine pangolins at a single North American zoological institution died or were euthanized with necropsy findings consistent with hepatic lipidosis, representing 9 of 14 mortalities during this time period.MethodsThis report describes hepatic lipidosis in these pangolins (clinical presentation, diagnostic imaging, clinicopathologic and postmortem findings) and summarizes clinically relevant predictors of disease.ResultsThe time from the onset of illness to death ranged from 2 to 75 days (median 23 days). Obesity was noted prior to clinical presentation for illness in 4/9 animals. All pangolins had anorexia and lethargy; other common clinical signs included constipation (6/9), vomiting or regurgitation (6/9), and/or dyspnea (5/9). Increased alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were observed in 7/9 animals, hyperbilirubinemia in 5/9, and increased bile acids in 5/9. Serum selenium was low in 3/9 animals, but vitamin E concentrations were normal. Hypertriglyceridemia was uncommon during illness (1/9). Evidence of renal dysfunction was also common, and included glucosuria (6/6), proteinuria (7/7), and azotemia (6/9). Ultrasound was the most reliable imaging technique at identifying hepatic lipidosis as evidenced by hepatomegaly and increased echogenicity. Despite variable treatment including assisted feeding, hepatoprotectants, fluid therapy, gastroprotectants, antibiotics, and/or antiemetics, all cases were ultimately fatal. Each of the animals had comorbidities or an inciting reason for anorexia that led to negative energy balance. In 5/9, resultant hepatic lipidosis was severe and deemed the primary cause of death or euthanasia.DiscussionThis case series suggests that white-bellied pangolins are prone to developing hepatic lipidosis following a period of anorexia secondary to other underlying disease processes. Elevated AST, ALT, bilirubin, and bile acids in an anorectic and lethargic pangolin should provide a high index of suspicion for hepatic lipidosis. Further study is needed to evaluate pangolins for potential unique polyunsaturated fatty acid or other species-specific dietary requirements.